Comparison of EMG Activation of Quadriceps Femoris on Different Static Squat Exercises in Young Men with Patellofemoral Syndrome - Yang, Jin-Hyeok; Lee, Su-Young (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study had the purpose to test the effect of using ball, and elastic band during static squat movement through EMG activation of quadriceps femoris in patellofemoral pain syndrome (PFPS) subjects. Methods/Statistical analysis: The participants was twenty-two men with PFPS. The subjects were randomly divided into basic squat exercise group, squat exercise using ball group, or squat exercise using elastic band group. While each static squat exercise was performed, EMG activities of quadriceps femoris was measured via surface electromyography (sEMG). One-way ANOVA was used to compare EMG activation of quadriceps femoris (rectus femoris, vastus medialis oblique, and vastus lateralis) of each group. Findings: The result showed that there was significantly different in vastus medialis oblique muscle activation among the groups (p<.05), while there was not significantly different in rectus femoris and vastus lateralis (p>.05). Vastus medialis oblique muscle activity showed a significant increase in the squat exercise with ball group relative to the basic squat exercise group (p<.05). The squat exercise with ball group showed the most increase in vastus medialis oblique muscle activation than rectus femoris and vastus lateralis (p<.05). The basic squat exercise and squat exercise with elastic band group didn’t have significant difference among three muscles (quadriceps femoris) (p>.05). However, in all groups, muscle activation increased in order of rectus femoris, vastus lateralis, and vastus medialis oblique. Improvements/Applications: This findings suggest that static squat exercise using ball can strengthen selective vastus medialis oblique muscle effectively that is necessary for patients with PFPS. In clinic, the use of the tool causing hip adduction during squat exercise may improve the effect.